Do Merger and Acquisition Affect on Company’s Financial Performance? - Novia Dian Larasati; Yuli Agustina; Lulu Nurul Istanti; Trisetia Wijijayanti (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
This research aims to determine whether there are differences in the company's financial performance before and after merger and acquisition are conducted. The design of this researchis quantitative research. This research was conducted on the listing company in the Indonesian Stock Exchange 2010-2014. The data source was obtained from secondary data; the data obtained from the financial conditionments. The total final samples used were 24 companies by usingpurposive sampling method. The data used were analyzed using the Wilcoxon Signed Ranked Test. The results of this research indicate that current ratio (CR),debt to equity ratio (DER),net profit margin(NPM),price earnings ratio (PER), total asset turnover (TATO) had no significant difference on the company before and after merger and acquisitionon the listing company in the Indonesian Stock Exchange (merger and acquisitionof 2010-2014).